Structural and functional insight into kinetochore protein CENP-N and its interaction with CENP-A nucleosome - Zhou, Keda, author; Luger, Karolin, advisor; Yao, Tingting, committee member; DeLuca, Jennifer, committee member; Bailey, Susan, committee member (Colorado State University. Libraries, 2018)
Proper chromosome segregation during mitosis is one of the most important processes to ensure genome integrity. During this process, the microtubules are captured by a multi-unit complex called kinetochore. The kinetochore is assembled specifically at centromere through recognizing nucleosomes containing the histone H3 variant CENP-A. CENP-N and CENP-C are the only two kinetochore proteins that specifically recognize CENP-A nucleosomes. There are about 1 in 25 nucleosomes that contain CENP-A at the centromere. Therefore, how these two proteins 'ignore' the abundant H3 nucleosomes to interact selectively with a handful of centromeric CENP-A nucleosomes has important implications for genome stability during cell division. To obtain deep insight into the mechanism behind this, I solved the structure of CENP-A nucleosome in complex with CENP-N by single particle cryo electron microscopy (cryo-EM) at 4 Å. Through charge and space complementarity, the unique "RG" loop on CENP-A is decoded by CENP-N. CENP-N also engages in extensive interactions with a long segment of the distorted nucleosomal DNA double helix. These interactions were validated in vitro and in vivo.The DNA ends of CENP-A nucleosome which are disordered in the crystal structure are mostly visible in the cryo-EM structure when it is in complex with CENP-N. By micrococcal nuclease digestion assay, the CENP-A nucleosome DNA ends are shown to be less flexible when CENP-N is presented in solution, which is consistent with structural study. Since CENP-N does not interact with DNA ends directly, the less dynamics on the DNA ends indicate a more stable nucleosome. By quantitative electrophoretic mobility shift assay (EMSA) and electron microscopy, the stabilizing effect of CENP-N on CENP-A nucleosome was confirmed in vitro. However, this effect was not significant in vivo, which indicates that the CENP-A nucleosome stability in vivo is determined by multiple factors. Besides the change on DNA ends of CENP-A nucleosome, the orientation of H4 N-terminal tail is altered due to its interaction with CENP-N, with important implications for the multiple biological processes involving the H4 N-terminal tail, especially with respect to the formation of chromatin higher order structure The structural and functional studies in this thesis shed light on how CENP-N ensures that the kinetochore assembles specifically at the centromere.